EFEKTIVITAS PELATIHAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP KUALITAS PENDIDIKAN ANAK USIA DINI - Karomah, Rosi; Ias Nugrahani; Ririn Duwila (Institut Agama Islam Negeri Bone, 2025)
Learning media becomes the main foundation in a teaching process. Technology is utilized to improve the quality of an educator. This study analyzes the effectiveness of technology-based learning media training and the quality of educators. The method used in this study is quantitative with a one-group pretest-posttest design to improve educator quality. The sample in this study consisted of 20 educators at RA Jambu. Data collection techniques were conducted through observation of pretest and posttest instruments by providing technology-based learning media training. Data analysis was conducted using the Normality Test, Homogeneity Test, and Paired Sample T-Test. The results of this study show that there is a positive and significant relationship between technology-based learning media training and educator quality. This article has implications for a quality leadership style that can address problems occurring in educational institutions.